The Reader's Digest children's atlas of the universe - Burnham, Robert, 1947- author (Pleasantville, N.Y. : Reader's Digest Children's Pub., 2000)
Includes star charts, maps, and satellite photos of the planets and coverage of such topics as distant galaxies and black holes as well as hands-on projects.